Pixel value differencing steganography techniques: Analysis and open challenge - Hussain, Mehdi; Wahab, Ainuddin Wahid Abdul; Anuar, Nor Badrul; Salleh, Rosli; Noor, Rafidah Md (2015)
Steganography is the science of secret data communication using carrier medium, such as images, videos, text, and networks. Image steganography is majorly divided into spatial and frequency domains. Pixel value differencing (PVD) considered as good steganographic algorithm due to its high payload and good visual perception in spatial domain. The purpose of this paper is two folded. First is the critical analysis of current PVD methods using evaluating parameters (payload, visual quality and resistance of attacks) and secondly it highlights the current promising directions on PVD steganographic research.